Influence of Cultural Factors on the Rate of School Dropout in Nangako Town Council, Bududa District - Loyce Nabutsale (Uganda Christian University, 2024)
This research report was undertaken to investigate on effect of cultural factors on the rate of school dropout in Nangako Town Council, Bududa District. It was guided by three objectives; to examine the effect of cultural norms on the rate of school dropout in Nangako Town Council, to determine the effect of cultural values on the rate of school dropout in Nangako Town Council, to assess the effect of cultural beliefs on the rate of school dropout in Nangako Town Council. This research used a sample size of 36 respondents, questionnaires and interview guide were used to collect data which was later analyzed using the statistical package for social sciences. Results of the first objective showed that cultural norms have a significant effect on the rate of school dropout in Nangako Town Council., Supported by the following responses; 44% strongly agreed, 22% agreed to the statement that societies with higher expectations for educational attainment tend to have lower dropout rates due to the perceived value and necessity of education; 25% strongly agreed, 19% agreed to the statement that societies that challenge gender biases and promote gender equality tend to have lower dropout rates among both boys and girls; 42% strongly agreed, 8% agreed to the statement that active parental engagement, such as monitoring academic progress. On the other hand,25% disagreed, 36% strongly disagreed constituting the majority were negative to statement that cultures that prioritize other aspects, such as early marriage or labor, may inadvertently discourage educational persistence, leading to higher dropout rates.Results of the second objective revealed that cultural values affect the rate of school dropout in Nangako Town Council and were supported by the following responses which include; 14% strongly agreed, 28% agreed to the statement that cultural values play a substantial role in shaping the attitudes and behaviors of individuals within a community. Supported by14% strongly agreed, 47% agreed to the statement that cultural beliefs that assign greater value to female domesticity and male breadwinning contribute to higher dropout rates among young women, 14% strongly agreed, 33% agreed to the statement that parental expectations and the persistence of cultural beliefs within ethnic communities can also be influential factors in the rate of school dropout. There is need to engage the community in promoting cultural values and increasing awareness about the importance of education. Organize cultural events within the community and involve students to showcase and celebrate their cultural heritage.
Undergraduate Research